The Efficacy and Safety of Roxadustat for Anemia in Patients With Chronic Kidney Disease: A Meta-Analysis - Lijun Wang; Heng Yin; Liling Yang; Fenglian Zhang; Song Wang; Dan Liao (Frontiers Media S.A., 2022)
Background: Chronic kidney disease (CKD) is a global public health problem, and anemia is a common complication in CKD patients. Roxadustat (FG-4592) is an oral hypoxia-inducible factor (HIF) stabilizer. Roxadustat has been shown in studies to keep up with and increase hemoglobin better than placebo or erythropoietin. The purpose of this meta-analysis was to assess the efficacy and safety of roxadustat.Methods: We searched CBM, CNKI, VIP, Wanfang Database, PubMed, Cochrane Library, Embase, and Web of Science for randomized controlled trials of roxadustat for the treatment of anemia in CKD patients. The papers were screened using rigorous criteria and their quality was assessed using the Cochrane 5.1.0 assessment manual for randomized controlled trials (RCTs). RevMan 5.3 was used to extract and synthesize data for meta-analysis.Results: There were 8 RCTs (7 articles) in all, and 1,364 patients with chronic kidney disease anemia were involved. The overall quality of the studies included was satisfactory. The meta-analysis findings revealed that roxadustat can considerably enhance hemoglobin, transferrin, and total iron binding capacity (TIBC) in both dialysis-dependent (DD) and non-dialysis-dependent (NDD) patients: Hemoglobin (Hb): DD: [SMD = 0.23, 95% CI (0.01, 0.44), p = 0.04], NDD: [SMD = 2.08, 95% CI (1.23, 2.93) p < 0.000001]; transferrin: DD: [SMD = 0.78, 95% CI (0.24, 1.32), p = 0.004], NDD: [SMD = 1.37, 95% CI (0.76, 1.98), p < 0.0001]; TIBC: DD [SMD = 0.97, 95% CI (0.64, 1.29), p < 0.00001], NDD [SMD = 1.34, 95% CI (0.9, 1.78), p < 0.00001]. After roxadustat therapy, patients' serum iron levels were considerably higher in the dialysis group than in the control group, but there was no significant change in the NDD group [SMD = 0.42, 95% CI (0.27, 0.57), p < 0.00001]. In the NDD group, hepcidin, ferritin, and transferrin saturation (TSAT) were significantly reduced after roxadustat treatment: Hepcidin [SMD = −1.59, 95% CI (−2.69, −0.49), p = 0.005], ferritin [SMD = −0.51, 95% CI (−0.72, 0.3) p < 0.00001], TSAT [SMD = −0.41, 95% CI (−0.62, 0.2), p < 0.0001]. In terms of safety, adverse events (AE) [SMD = 1.08, 95% CI (0.98, 1.18) p = 0.11] and serious adverse events (SAE) [SMD = 1.32, 95% CI (0.97, 1.9) p = 0.08] were not significantly different between the two groups.Conclusion: Roxadustat can improve anemia in NDD patients with chronic kidney disease, and its short-term safety was comparable to that of the comparison group.